Manipulation of extinction features in frequency combs through the usage of graphene - Barturen, Mariana (2018)
Lately, the integration of two-dimensional materials into semiconductor devices has allowed the modification of their e ective index by simply applying a modest voltage (between 0 and 3 volts). In this work, we present a device composed of two evanescently coupled silicon microring resonators where both rings have a graphene layer on top. This design is aimed to produce frequency combs with transmission characteristics controlled upon voltage application to the graphene layer. We numerically analyze the device response as a function of the incident wavelength and applied voltage. The results showed a low input intensity (0.6 GW/cm2) needed and a rapid response time (0.1 µs), in comparison to devices controlled by heat injection.